PENGEMBANGAN KOMPETENSI PROFESIONAL GURU DI SEKOLAH MENENGAH ATAS NEGERI 1 KOTA BENGKULU - Apandi; Syaiful Anwar (Manajer Pendididikan, 2022)
his research aims to determine the development of teachers’ professional competency, such as how teachers in Guru City from SMAN 1 apply good philosophical, psychological and sociological education foundations, apply learning theories, and use interesting learning methods according to the level of development of students, teachers can develop and use various tools, media, and related learning resources, teachers can evaluate students' learning outcomes, and how teachers at SMAN 1 Bengkulu City develop their skills and insights. The methods used are descriptive quantitative and survey methods. The population and sample are 50 civil servant teachers of SMAN 1 in Bengkulu City. Data collection techniques using questionnaires and interviews. The research results show that the professional competence of SMAN 1 teachers is well developed. Demonstrate their skills and insights in seminar activities/soft skills training. Suggestions are given to teachers that they must continue to develop their professional competences by honing their skills and insights in workshop activities / soft skills training.